Sri Lankans' Views on English in the Colonial and Post-Colonial Eras - Ramesh, Subathini (Cambridge Scholars Publisher, 2020)
This book evaluates the views of different ethnic groups towards the English language in Sri Lanka for a period of almost two centuries. While a few studies have addressed the subject of English in Sri Lanka in a general way, there has been no research showing the specifics of English usage in the major ethnic communities of the country. This text considers notions and attitudes towards English that prevail in Sri Lanka today among writers, language planners, teachers and students, habitual speakers, and infrequent users, as well as elite and non-elite groups in the country. The book also exam.